Correlates and Consequences of Degree Purchasing among Canadian University Students - Brotheridge, Celeste M.; Lee, Raymond T. (Canadian Journal of Higher Education, 2005)
This article develops the construct of degree purchasing as an instrumental orientation towards education in which students value education primarily as a vehicle for labour market participation rather than as an avenue for learning. This study of 188 Canadian university students found that a substantial proportion of students tended to be more interested in acquiring a diploma than the learning that it represents. Female students were more instrumentally oriented than male students, and younger students devalued learning to a greater extent than older students. Finally, a degree purchasing orientation was associated with poor study habits, the use of resistance strategies in the classroom, low positive affect, and poor course performance. Implications for higher education and suggestions for future research are discussed.